Training on Basic Dribbling Techniques for Basketball Players at the JBC Club - Ahmad, Nurdian; Wahyu Sulistyo, Yully (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
The aim of this service research is to provide an understanding of the basic techniques of basketball dribbling at the JBC basketball club in Jombang Regency. lack of understanding of the basic basketball dribbling techniques that underlie the implementation of community service research. The basic technique of dribbling is very important because the basic capital of the game of basketball is dribbling. Correct understanding of basic dribbling techniques will make the activity more effective and make players more quickly practice basketball dribbling movements, whereas incorrect understanding makes activities less effective and there are many mistakes in practicing basic dribbling techniques. The target of this program is the JBC basketball club players totaling 50 players. Meanwhile, this activity program provides basketball dribbling training, the methods used are: 1. Discussion with the players and showing videos of basic basketball dribbling techniques, 2. Dribbling practice on the field divided into several groups. From the results of the service implementation, many players were able to practice movements and various basic dribbling techniques well and correctly, providing good understanding and motivation made the enthusiasm of the players increase so that the service implementation could run smoothly according to the targets to be achieved.